Medial Plantar Artery Flap: A Boon for Weight Bearing Sole Defects - Vaghani, Sanjay Gordhanbhai; Chaudhari, Ganesh Sadashiv (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Healthy Sole is an indispensable structure of the foot for carrying the weight of one's body. Any injury or structural damage to the weight-bearing sole makes a person cripple. In literature, multiple reconstructive alternatives are described ranging from skin graft and pedicled flap to microvascular free tissue transfer. The author reported a variety of etiological factors leading to sole defects. The leading cause of sole defects was Post debridement defects in the diabetic foot. Other causes were post-resection/ excision defects in melanoma and squamous cell carcinoma lesions. Solitary cases of postelectric burn defects were also reported in this study. This study reports seven Heel defect cases & 3 forefoot defects. Heel defects were reconstructed with a proximally based medial plantar flap while forefoot defects were with a distally based flap. Sizes of flaps ranged from 5x5 cm to 10x7 cm. This flap offered stable, durable, Robust and cosmetically acceptable tissue cover for small to medium size weight bearing sole defects.